(untitled) (Revista de Ciências Agroveterinárias, 2019)
The sprinkler irrigation reduces the negative effects of water deficit and increases the yield and performance of soybean seeds on field. Thus, the objective of work was to evaluate the effect of sprinkler irrigation on yield and physiological potential of soybean seeds produced in lowland soils. The treatments consisted of 8 soybean cultivars and two water regimes: with and without sprinkler irrigation. This work was developed using soybean seeds of the cultivars BMX Força RR, BRS Tertúlia RR, CD 249 RR STS, BMX Potência RR and BRS 246 RR, BRS Charrua RR, BRS Taura RR, and CD 231 RR. The variables analyzed were the seeds yield, germination, first count of germination, accelerated aging, electrical conductivity, field emergence, and seed weight. The sprinkler irrigation on soybean crop in lowland soil increase in seed yield of all cultivars studied, the increase varied from 32% to 139%. The sprinkler irrigation has improved seed performance of cultivars BMX Força RR, BRS Tertúlia RR, CD 249 RR STS, BMX Potência RR, and BRS Taura.